2015
DOI: 10.3402/meo.v20.24245
|View full text |Cite
|
Sign up to set email alerts
|

Does emotional intelligence predict breaking bad news skills in pediatric interns? A pilot study

Abstract: BackgroundWhile both patients and physicians identify communication of bad news as an area of great challenge, the factors underlying this often complex task remain largely unknown. Emotional intelligence (EI) has been positively correlated with good general communication skills and successful leadership, but there is no literature relating EI to the delivery of bad news.PurposeOur objectives were to determine: 1) performance of first-year pediatric residents in the delivery of bad news in a standardized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…The majority of these feelings were also reported by the participants in this study. Because our study participants were educated and skilled, they could manage their negative feelings related to the CPR situation, which was consistent with the findings of Reed et al (). Elliot () stated that avoiding negative stimuli affects energy levels in individuals, which was consistent with the category of “avoiding undesirable social outcomes” developed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of these feelings were also reported by the participants in this study. Because our study participants were educated and skilled, they could manage their negative feelings related to the CPR situation, which was consistent with the findings of Reed et al (). Elliot () stated that avoiding negative stimuli affects energy levels in individuals, which was consistent with the category of “avoiding undesirable social outcomes” developed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Another study in pediatrics found no correlation between EI and skills in breaking bad news. 27 Gorgas et al 28 explored the efficacy of a social awareness training program for emergency medicine residents. The authors report a delayed but significant increase in EI after the intervention.…”
Section: Themes In Nonsurgical Literaturementioning
confidence: 99%
“…Likewise, although EI is a specific entity, facets of the concept are likely addressed in other literature that 19 x Lin et al 17 x x Chan et al 16 x x Dugan et al 20 McKinley et al 18 x x Arenja et al 15 x McKinley et al 4 x x Satterfield et al 21 Blumenthal et al 22 Louie et al 25 Johnson and Stern 24 x Schrimpf and Trief 23 x Olson et al 26 x Reed et al 27 x Gorgas et al 28 x would not be captured through our search design. Regardless, EI is a concept that has been embraced by the business community, has been increasing in popularity in the medical field, and is evidently a new trend in the surgical education literature.…”
Section: Study Weaknessesmentioning
confidence: 99%
“…As discovered by Reed et al when studying residents in their first year of training high EI scores were not correlated with an increased ability to deliver bad news. 24 They concluded that increased resident EI does not replace specific training in the delivery of bad news. 24 In the design of EI-related learning sessions, a systematic review by Cherry et al provided suggestions for the structure of this training.…”
mentioning
confidence: 99%
“…Systematic reviews have demonstrated that although many people are writing opinion pieces on EI and completing descriptive studies, there are actually very few empirical studies linking a doctor's skill or competence with EI or studies showing how high EI is correlated with improved patient outcomes. 9,10,[24][25][26] One of the only studies to do this is by Wagner et al and included 30 residents and family physicians at an academic family medicine institution and only showed the subscale Happiness, as measured by the EQ-i©, to be correlated with improved patient satisfaction. 10 Our descriptive study may be used as a starting point for further investigation into the impact of EI on patients and families cared for by pediatric residents.…”
mentioning
confidence: 99%